Downregulation of Thromboxane A2 Receptor Occurs Mainly via Nuclear Factor-KappaB Signaling Pathway in Rat Renal Artery - Yaping Zhang; Man Mi; Yan-Hua Xie; Si-Wang Wang; Lars Edvinsson; Cang-Bao Xu (Hindawi Limited, 2017)
Thromboxane A2 (TXA2) acts on TXA2 receptors (TP) to regulate renal artery blood flow and subsequently contributes to the pathogenesis of renal ischemia. The present study was designed to examine if nuclear factor-kappaB (NF-κB) signaling pathway is involved in the downregulation of TP receptors in rat renal artery. Rat renal artery segments were organ cultured for 6 or 24 h. Downregulation of TP receptors was monitored using myograph (contractile function), real-time PCR (receptor mRNA), and immunohistochemistry (receptor protein). Specific inhibitors (MG-132 and BMS345541) for NF-κB signaling pathway were used to dissect the underlying molecular mechanisms involved. Compared to fresh (noncultured) segments, organ culture of the renal artery segments for 24 h induced a significant rightward shift of U46619 (TP receptor agonist) contractile response curves (pEC50: 6.89±0.06 versus 6.48±0.04, P<0.001). This decreased contractile response to U46619 was paralleled with decreased TP receptor mRNA and protein expressions in the renal artery smooth muscle cells. Specific inhibitors (MG-132 and BMS345541) for NF-κB signaling pathway significantly abolished the decreased TP protein expression and receptor-mediated contractions. In conclusion, downregulation of TP receptors in the renal artery smooth muscle cells occurs mainly via the NF-κB signaling pathway.